Is the diet important for psoriasis? - Owczarczyk-Saczonek, Agnieszka; Placek, Waldemar (Dermatology Review/Przegląd Dermatologiczny, 2014)
Psoriasis is a systemic disease, associated with the occurrence of metabolic disorders (obesity, diabetes, hyperuricemia, lipid disorders) and rapid development of atherosclerosis; therefore diet can be an important adjuvant therapy. A low-calorie diet is an important complement treatment of patients with psoriasis, particularly those with concomitant obesity. There are a lot of studies indicating that obesity is a risk factor for psoriasis and vice versa. Visceral adipose tissue produces numerous proinflammatory cytokines (TNF-α, IL-6, Il-8, Il-17, Il-18), the same ones that participate in development of psoriatic lesions. Important factors in the diet are the essential polyunsaturated omega-3 fatty acids. They have an anti-inflammatory effect because they inhibit the production of proinflammatory cytokines (I-1b, IL-6, IL-8, TNF-α) and adhesion molecules (ICAM-1, VCAM-1). In addition, supplementation of omega-3 and natural antioxidants in the diet may help to reduce "oxidative stress" and systemic inflammation. The use of a gluten-free diet is controversial, but in patients with positive anti gliadin antibodies it seems justified. An essential element of the procedure is to avoid alcohol and all its forms and stimulants that have pro-inflammatory effects. We should advise our patients to avoid grapefruit juice during treatment with cyclosporine and limit the supply of simple sugars, animal fats and alcohol during treatment with retinoids. Dietary recommendations for patients with psoriasis are an important part of a holistic approach to patients who expect comprehensive care, not just the prescription.